First surgical experience with a COVID-19 positive patient in Costa Rica: case report, staff safety protocol and brief review of literature - Alfredo Sanchez-Betancourt; Pablo Sibaja-Alvarez; Milagros Gonzalez-Cole; Ivannia Mendez-Barboza; Crishtna Ledezma-Cruz; Priscilla Vargas-Paez (Surgical Case Reports)
Abstract Background The safe management of patients with COVID-19 has been a challenge during the current pandemic, leading to healthcare workers being disproportionately affected by the virus. In Costa Rica, 20% of all infections and 27% of all ICU cases during the initial weeks of the outbreak were healthcare workers. The existing recommendations and protocols on how to care for an infected patient that requires acute surgical management have been applied successfully in various scenarios. We look to describe the first case of a COVID-19 patient that required surgical management in Costa Rica and present a summary of the protection measures utilized in a tertiary care hospital. Materials and methods A review of literature utilizing Embase, Medline Complete and Google Scholar was performed. A surgical case report using the SCARE statement guidelines was drafted and a brief summary of the 54 items contained in the hospital’s COVID-19 surgical protocol is described. Case presentation We present the case of a 29 year old obese male who had acute appendicitis with perforation that contracted SARS-CoV-2 and became symptomatic at home on pod#3, who later required multiple surgeries to address an infected abdominal hematoma both while having an active COVID-19 infection and afterwards. Conclusions Safety measures for both staff and patients are of the utmost importance during the current coronavirus pandemic. Limitations in the availability of personal protection equipment as well a lack of knowledge and experience with handling surgical patients with this condition have led to various safety and attention protocols being drafted. The successful management of this patient is the first experience in Costa Rica on how to properly address staff safety during a surgical procedure. None of the workers involved in care of this patient were diagnosed with SARS-CoV-2.